Asprosin impairs insulin secretion in response to glucose and viability through TLR4/JNK-mediated inflammation - Lee, Taeseung; Yun, Subin; Jeong, Ji Hoon; Jung, Tae Woo (Molecular and cellular endocrinology, 2019)
Severe inflammation in the islets is observed in obese patients with type 2 diabetes. Inflammation in the islets is caused by obesity-induced serum free fatty acids. Asprosin is a fasting-induced adipokine, which contributes to hepatic glucose production. However, the effects of asprosin on inflammation and cellular dysfunction in pancreatic β-cells remain to be elucidated. Here, we demonstrated that treatment of mouse insulinoma MIN6 cells and human primary islets containing β-cells with palmitate increased asprosin expression and secretion. Treatment of MIN6 cells and human primary islets with palmitate increased phosphorylation of the inflammatory marker nuclear factor-kappa B (NFκB) and the release of pro-inflammatory cytokines including TNF and MCP-1 and decreased glucose-stimulated insulin secretion and cell viability. However, siRNA-mediated suppression of asprosin reversed these changes. Recombinant asprosin treatment of MIN6 cells and human primary islets augmented the inflammation response, cellular dysfunction, and apoptosis in a dose-dependent manner. Asprosin induced toll-like receptor (TLR) 4 expression and JNK phosphorylation. siRNA for TLR4 or JNK mitigated the effects of asprosin on inflammation and cellular dysfunction. These results suggest that palmitate-derived asprosin secretion from β-cells results in their inflammation and dysfunction through a TLR4/JNK-mediated pathway. This report suggests asprosin as a novel therapeutic target for the treatment of type 2 diabetes through preservation of β-cell function. [Display omitted] •Palmitate augments asprosin expression in and palmitate group.•Asprosin promotes inflammation in sion in.•Asprosin induces cellular dysfunction apoptosis in tate gr.•Asprosin binds to TLR4 to stimulate JNK phosphorylation.•TLR4/JNK-mediated pathway plays an important role in asprosin-induced inflammation, cellular dysfunction, and apoptosis in β-cells.